Convalescent plasma for treatment of COVID-19: study protocol for an open randomised controlled trial in Sweden - Joakim Dillner; Johan Ursing (BMJ Open)
Introduction Although there are many studies on the use of convalescent plasma (CP) for treatment of COVID-19, it is not clear (1) which groups of patients may benefit, (2) what dose of plasma to give, or (3) which antibody levels the plasma should contain. Previous phase I/II studies and literature review suggest that CP should only be given to patients with viraemia, that a daily infusion should be given until the patient becomes virus free and that the neutralising antibody titre should preferably be >1:640Methods and analysis An open randomised controlled trial enrolling patients with COVID-19, who must be SARS-CoV-2 positive in both airway and blood samples and admitted to a study hospital. Block randomisation 2:1 is to either 200 mL CP (preferably titre ≥1/640) daily for up to 10 days (until virus negative in blood) plus standard care or standard care only (control arm). The primary endpoint is mortality by day 28 after study inclusion. Secondary endpoints include mortality by day 60 and doses of plasma needed to clear viraemia. Assuming a reduced mortality of approximately 30% by the CP therapy and 85%–88% survival in the control arm, approximately 600 participants will be enrolled to the CP therapy arm and 300 participants to the control arm.Ethics and dissemination Ethical approval has been granted by the Swedish Ethical Review Authority (reference: 2020-06277). Results from this trial will be compiled in a clinical study report, disseminated via journal articles and communicated to stakeholders.Trial registration number NCT04649879.